Antipneumococcal Activities of a Ketolide (HMR 3647), a Streptogramin (Quinupristin-Dalfopristin), a Macrolide (Erythromycin), and a Lincosamide (Clindamycin) - Barry, A. L. (American Society for Microbiology, 1998)
Four different compounds belonging to the macrolide-lincosamide-streptogramin B (MLS(b)) class of antimicrobial agents were tested against 611 Streptococcus pneumoniae strains. The ketolide (HMR 3647, previously RU66647) and the streptogramin (quinupristin-dalfopristin) were both active against pneumococci with high-level MLS(b) resistance (clindamycin-resistant strains) as well as those with low-level macrolide resistance (clindamycin-susceptible strains).